Banking security synergetic models - Hryshchuk, Ruslan; Yevseiev, S. P.; Romashchenko, Nataliia (My University, 2019)
The revolutionary changes of the last decade in the banking sector have led to the blending of information and computer networks into a single information and cybernetic space, which has led to the creation of automated banking systems (ABS), which have expanded the range of state electronic services and commercial banks of the world and Ukraine. As a result, threats to such national information resource of the state as banking information resources (BIR). Security threats BIR acquired signs of hybridization. Signs of hybridity as a result of simultaneous exposure to information security threats, cybernetic security (CS) and information security (InfoSec) to BIR led to the emergence of a synergistic phenomenon whose negative signs require a radical overhaul of the concepts of existing security systems development. The article proposes mathematical methodology models for building the BIR security based on the synergistic approach of estimating hybrid threats. The proposed model forms a complex approach to assessing the current level of BIR security in the ABS, assessing the economic feasibility of introducing one or another mechanism of Technical means of InfoSec system in the ABS, depending on the banking information value, based on an advanced threat classifier.
Keywords: article synergistic threat model; information security of banking information; threats to bank information resources; automated banking systems